Dampak Investasi Infrastruktur Terhadap Pertumbuhan Ekonomi Di Pulau Jawa - Risca Dwi Anggini; Teguh Hadi Priyono; Riniati; Fathorrazi, Moehammad (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
Economic growth is a sign to achieve development success economy in society. Investment is considered as one of the factors that can increase economic growth. So it must be equipped with supporting investments this is called infrastructure investment. Economic growth and the rate of movement of a country or within the scope of the region cannot be separated from the availability of economic infrastructure, such as electricity, gas, water, transportation, warehouse, telecommunications. This study aims to determine the impact of infrastructure investment on economic growth in Java. This type of research data uses secondary data, namely: panel data consisting of time series data for 2011-2020 and cross section data for 5 provinces in Indonesia. Java Island. Data analysis using multiple regression. The results showed that PMA variables on electricity, gas and water infrastructure have a positive and not significant effect to economic growth. While the PMDN variable in electricity, gas and electricity infrastructure water, PMA variable in transportation, warehouse and telecommunications infrastructure, and variable Domestic Direct Investment in transportation, warehouse and telecommunications infrastructure has a negative and significant effect on economic growth.